Feasibility of Tomotherapy-based image-guided radiotherapy for small cell lung cancer - Nguyen, Nam P.; Shen, Wei; Kratz, Sarah; Vock, Jacqueline; Vos, Paul; Vinh-Hung, Vincent; Altdorfer, Gabor; Ewell, Lars; Jang, Siyoung; Karlsson, ULF L.; Godinez, Juan; Mills, Melissa; et al. (Frontiers in Oncology, 2013)
Background: To assess the tolerance of patients with small cell lung cancer undergoing chemoradiation with tomotherapy-based image-guided radiotherapy (IGRT). Materials and methods: A retrospective review of the toxicity profile for nine patients with small cell lung cancer of the limited stage who underwent chemoradiation delivered with helical tomotherapy (HT) has been conducted. Results: Acute grade 3-4 hematologic and esophagitis toxicities developed in two and three patients respectively. One patient developed a pulmonary embolism during radiotherapy. Seven patients had weight loss ranging from 0 to 30 pounds (median: 4 pounds). Three patients had treatment breaks ranging from 2 to 12 days. At a median follow-up of 11 months (range: 2-24 months), no patients developed any radiation related toxicities such as grade 3-4 pneumonitis or other long-term complications. The median survival was estimated to be 15 months. There were 2 local recurrences, 3 mediastinal recurrences, and six distant metastases. Conclusion: Grade 3-4 toxicities remained significant during chemoradiation when radiation was delivered with tomotherapy-based IGRT. However, the absence of grade 3-4 pneumonitis is promising and the use of HT needs to be investigated in future prospective studies.